Sleep in ring chromosome 20 syndrome: a peculiar electroencephalographic pattern - Zambrelli, Elena; Vignoli, Aglaia; Nobili, Lino; Didato, Giuseppe; Mastrangelo, Massimo; Turner, Katherine; Canevini, Maria Paola (Functional neurology, 2013)
Ring chromosome 20 [r(20)] syndrome is a chromosomal disorder characterized by epilepsy and intellectual disability. Distinctive electroclinical features and wakefulness EEG patterns have been described. The EEG features of sleep have not yet been evaluated. We studied the pattern of sleep in six patients aged 2-59 years who underwent at least one polysomnographic recording. Their sleep pattern evolution is described as deterioration ranging from normal to destructured NREM/REM sleep. NREM sleep alterations were observed from childhood and were more evident in adulthood. EEG abnormalities detected during wakefulness persisted, with morphological changes, during sleep. During NREM sleep all the subjects presented high amplitude delta sequences with a sharply contoured or notched appearance, prevalent over frontal regions. The theta rhythm of wakefulness was seen to persist during REM sleep. Ring chromosome 20 syndrome shows sleep alterations that seem to be age-related. A potential role of cortical and thalamocortical dysfunction is discussed.